Characteristics of pressure waves radiated from tunnel portals in cuttings. (17th March 2022) - Wang, Honglin; Vardy, Alan E.; Bi, Haiquan
Highlights: Strong pressure radiation from tunnel exit portals in cuttings is investigated. Differences between 2-D and 3-D radiation strongly influence the outcomes. In some above-ground locations, pressures exceed those from above-ground portals. Elsewhere, funneling effects of cuttings tend to protect above-ground locations. Transition from 3-D to 2-D radiation is found to cause oscillatory behavior. Abstract: The radiation of pressures from the portal of a railway tunnel in a cutting is investigated to determine how consequential disturbances experienced at ground level compare with those from an above-ground portal. As might be expected intuitively, the above-ground amplitudes of disturbances from below-ground portals tend to be smaller than those from above-ground portals. However, this is not true in locations close to the cuttings themselves. The mixed outcomes are explained by analogy with known differences between wave propagation cylindrical (2-D) domains and more open spherical (3-D) domains that are commonly used to model the radiation of pressures from above-ground portals. Four cuttings are considered. It is shown that cylindrical-like behavior is pronounced for deep, narrow cuttings and that its influence can be significant even in shallow wide cuttings. The main body of the paper is focussed on conditions that would be experienced in locations at ground level, but one section is dedicated to an assessment of conditions close to track level where the amplitudes of the disturbances are much greater.